Tracheal compression as a cause of respiratory symptoms after repair of oesophageal atresia. Issue 3 (March 1978) - Cook, R C; Bush, G H
Abstract : A case of tracheal compression in an infant after repair of a tracheo-oesophageal fistula and oesophageal atresia is reported. Tracheopexy completely relieved the symptoms of apnoeic attacks, cyanosis, and convulsions. We suggest that tracheal compression in infants and children with repaired oesophgeal atresia can not only cause life-threatening attacks but also be responsible for recurrent chest infections. All infants and children with signs and symptoms of tracheal compression as shown by the presence of a barking type of cough, recurrent chest infections, or persistent mild respiratory symptoms should be referred for thorough investigation of the tracheobronchial tree.